النظرية الاجتماعية ومشكلات توظيفها في مراحل البحث الاجتماعي - مداح، سليمان (University Of Eloued جامعة الوادي, 2022)
Scientific theory has a distinct place in scientific research. Theory and research are like body and soul. They cannot be separated. The relationship between them is a complementary relationship, and this is what applies to social theory and social research. Accordingly, this intervention came with the aim of clarifying the social theory and the conditions for its construction and its importance in social research, as well as the steps to employ it according to the stages of the research. In order to answer this problematic, we will try to elicit and derive problems through the conditions of building the theory and the stages of its use, as well as its objectives in each step of the social research, and accordingly we offer some suggestions and advice that would avoid or reduce these obstacles that the researcher encounters while applying the theory in his study.
مداخلة
Keywords: بحث علمي; بحث اجتماعي; نظرية اجتماعية; مقاربة نظرية; Scientific research; social research; social theory; theoretical approach